Li₂Zn₂(MoO₄)₃ crystal as a potential detector for ¹⁰⁰Mo 2β-decay search - Bashmakova, N.V.; Danevich, F.A.; Degoda, V.Ya.; Dmitruk, I.M.; Kudovbenko, V.M.; Kutovyi, S.Yu.; Mikhailin, V.V.; Nagorny, S.S.; Nikolaiko, A.S.; Nisi, S.; Pavlyuk, A.A.; Pirro, S.; et al. (Functional Materials, 2009)
Properties of Li₂Zn₂(MoO₄)₃ crystals grown by the low-thermal-gradient Czochralski technique have been studied. Chemical composition of the material was tested by ICP-MS mass-spectrometry. Optical properties (refraction, transmittance and reflectivity) have been measured. Luminescence characteristics of crystals under ultraviolet, synchrotron, and X-ray excitation has been studied. Properties and the applicability of Li₂Zn₂(MoO₄)₃ crystals as scintillation and bolometric detectors have been checked for the first time. Досліджено властивості кристалів Li₂Zn₂(MoO₄)₃, вирощених методом Чохральського з низьким температурним градієнтом. Хімічний склад зразків перевірено за допомогою ICP-MS мас-спектрометрії. Виміряно оптичні характеристики (заломлення, прозорість та відбивання). Люмінесцентні характеристики кристалів досліджено при збудженні ультрафіолетовим, синхротронним та рентгенівським випроміненнями. Вперше перевірено можливості використання кристалів Li₂Zn₂(MoO₄)₃ як сцинтиляційних та болометричних детекторів. Изучены свойства кристаллов Li₂Zn₂(MoO₄)₃, выращенных методом Чохральского с низким температурным градиентом. Химический состав проверен при помощи ICP-MS масс-спектрометрии. Измерены оптические свойства (преломление, прозрачность и отражение). Люминесцентные характеристики кристаллов изучены при возбуждении ультрафиолетовым, синхротронным и рентгеновским излучениями. Впервые проверены возможности использования кристаллов Li₂Zn₂(MoO₄)₃ в качестве сцинтилляционных и болометрических детекторов.